Simulation of pulsatile flow of blood in stenosed coronary artery bypass with graft - B. Wiwatanapataphee (2018)
In this paper, we investigate the behavior of the pulsatile blood flow in a Stenosed right coronary artery with a bypass graft. The human blood is assumed to be a non-Newtonian fluid and its viscous behavior is described by the Carreau model. The transient phenomena of blood flow though the stenosed region and the bypass grafts are simulated by solving the three dimensional unsteady Navier-Stokes equations and continuity equation. The influence of the bypass angle on the flow interaction between the jet flow from the native artery and the flow from the bypass graft is investigated. Distributions of velocity, pressure and wall shear stresses are determined under various conditions. The results show that blood pressure in the stenosed artery drops dramatically in the stenosis area and that high wall shear stresses occur around the stenosis site.